Mercury Chloride (II) genotoxicity in Oreochromis niloticus (Pisces, Cichlidae) fingerlings exposed to different temperatures - Francia-Quiroz, Juan Carlos (2023)
Mercury chloride (HgCl2) is a neurotoxic, nephrotoxic, and genotoxic compound found in aquatic environments due to anthropogenic activities and whose effect can be altered by variations in temperature (for example: global warming). The aim of this work was to determine the mean lethal concentration (LC50) for HgCl2 and its genotoxic effect, in relation to the increase in temperature for Oreochromis niloticus fingerlings. The LC50 results for HgCl2 during the exposure times (48, 72, and 96 h) and temperatures (28 and 32 °C) showed that the LC50-96h increased from 0.39 mg L-1 for 28 °C to 0.66 mg L-1 for 32 °C. For sublethal evaluation, HgCl2 concentrations from LC50-96h were established for 28 and 32 °C, evaluating genotoxicity for 30 days through the nuclear abnormalities (AN) and micronucleus (MN) assay. A higher frequency of AN and MN was observed at 0.07 mg L-1 of HgCl2 for 32 °C. It is concluded that the LC50 and genotoxicity (AN and MN) for HgCl2 increase with increasing temperature from 28 to 32 °C.